Study of transformer coupled toroidal discharges - González, Juan José, author; Collins, George, advisor (Colorado State University. Libraries, 2005)
The technology of transformer-coupled toroidal discharges (TCTD) has grown to become a key element in the semiconductor industry, especially in applications such as remote chamber cleaning and remote generation of reactive gases. This Dissertation provides a description of TCTDs from two different perspectives. On the one hand, it studies the basic mechanisms of power deposition into the plasma and the processes occurring in the plasma bulk, completing the physical description of the plasma by describing its interaction with the wall and the properties of the plasma sheath. On the other hand, this work analyzes the properties of TCTDs from an electrical point of view, investigating the scaling laws that guide their design and exploring the technical obstacles that must be cleared to develop industrial remote plasma sources. In the first part of this work, we will describe the electrical characteristics and basic plasma bulk physics of TCTDs. The description includes a model for the plasma bulk that incorporates the most relevant mechanisms for the range of pressure and power density of interest. The results of this model are contrasted against experimental measurements carried out in TCTDs. In the second of this Dissertation, we present a simple model that describes the temporal variation of voltage and current across the sheath and along the chamber in conductive and dielectric vessels. The good agreement observed between the models predictions and experimental data from argon discharges shows that both models succeeds in capturing the essential aspects of the plasma bulk and its interaction with the walls.
Keywords: fluid dynamics; gases; plasma physics